Collaborative Academic Supervision as an Effort to Optimize Teacher Performance in the Independent Curriculum - Subagio, Agus; Waruwu, Marinu; Enawaty, Eny; Halida, Halida (Universitas Syiah Kuala, 2024)
This study explores the role of collaborative academic supervision in optimizing teacher performance within the framework of the Independent Curriculum. The Independent Curriculum, implemented in Indonesia, emphasizes student-centered learning and encourages teachers to adopt innovative teaching strategies. However, effective implementation requires a supportive environment, where academic supervision plays a crucial role. This research employs a qualitative approach, utilizing interviews and focus group discussions with educators and school administrators from various educational institutions. The findings reveal that collaborative academic supervision fosters a culture of shared responsibility among teachers, enhancing their professional development and instructional practices. Participants reported that engaging in collaborative supervision activities, such as peer observations and joint lesson planning, significantly improved their teaching efficacy and motivation. Furthermore, the study highlights the importance of building strong relationships among educators, as trust and open communication are essential for effective collaboration. The research also identifies challenges, including time constraints and varying levels of commitment among teachers, which can hinder the effectiveness of collaborative supervision. Based on these findings, the study recommends that schools prioritize collaborative academic supervision by providing structured training and allocating time for teachers to engage in these activities. This approach not only improves teacher performance but also contributes to a more dynamic and responsive learning environment for students. Overall, this research underscores the significance of collaborative academic supervision as a strategy to optimize teacher performance and enhance the quality of education within the Independent Curriculum framework.